Quality metrics and outcomes among critically ill patients in China: results of the national clinical quality control indicators for critical care medicine survey 2015–2019. Issue 9 (5th May 2022) - Rui, Xi; Dong, Fen; Ma, Xudong; Su, Longxiang; Shan, Guangliang; Guo, Yanhong; Long, Yun; Liu, Dawei; Zhou, Xiang; ,
Abstract : Background: It is crucial to improve the quality of care provided to ICU patient, therefore a national survey of the medical quality of intensive care units (ICUs) was conducted to analyze adherence to quality metrics and outcomes among critically ill patients in China from 2015 to 2019. Methods: This was an ICU-level study based on a 15-indicator online survey conducted in China. Considering that ICU care quality may vary between secondary and tertiary hospitals, direct standardization was adopted to compare the rates of ICU quality indicators among provinces/regions. Multivariate analysis was performed to identify potential factors for in-hospital mortality and factors related to ventilator-associated pneumonia (VAP), catheter-related bloodstream infections (CRBSIs), and catheter-associated urinary tract infections (CAUTIs). Results: From the survey, the proportions of structural indicators were 1.83% for the number of ICU inpatients relative to the total number of inpatients, 1.44% for ICU bed occupancy relative to the total inpatient bed occupancy, and 51.08% for inpatients with Acute Physiology and Chronic Health Evaluation II scores ≥15. The proportions of procedural indicators were 74.37% and 76.60% for 3-hour and 6-hour surviving sepsis campaign bundle compliance, respectively, 62.93% for microbiology detection, 58.24% for deep vein thrombosis prophylaxis, 1.49% for unplanned endotracheal extubations, 1.99% for extubated inpatients reintubated within 48 hours, 6.38% for unplanned transfer to the ICU, and 1.20% for 48-hour ICU readmission. The proportions of outcome indicators were 1.28‰ for VAP, 3.06‰ for CRBSI, 3.65‰ for CAUTI, and 10.19% for in-hospital mortality. Although the indicators varied greatly across provinces and regions, the treatment level of ICUs in China has been stable and improved based on various quality control indicators in the past 5 years. The overall mortality rate has dropped from 10.19% to approximately 8%. Conclusions: The quality indicators of medical care in China's ICUs are heterogeneous, which is reflected in geographic disparities and grades of hospitals. This study is of great significance for improving the homogeneity of ICUs in China.